Beyond the Double Helix: Emerging Trends in Forensic DNA Technologies - Labhini Rahangdale (AG Volumes, 2026)
Advances in forensic DNA technology have been remarkable, growing from the use of classic DNA profiling to sophisticated molecular technologies that deliver full genetic information for criminal investigations and human identification. This review discusses the development of forensic DNA technologies that have transcended the original model of the DNA double helix, covering recent advances in DNA profiling, sequencing and new molecular technologies. Forensic DNA technologies have advanced greatly, most notably through the use of Forensic Investigative Genetic Genealogy (FIGG), Short Tandem Repeat (STR) profiling, Rapid DNA, Next-Generation Sequencing (NGS), Single Nucleotide Polymorphism (SNP) analysis, forensic DNA phenotyping, epigenetic markers, microbial forensics, and environmental DNA. The review also explains how these technologies are used in crime scene investigation, disaster victim identification, missing persons, forensics in wildlife and cold case resolution. Finally, it critically scrutinises the ethical, legal and scientific issues of the use of advanced forensic DNA in the Indian context, highlighting the importance of proper governance, standardisation and responsible implementation.